Treinamento de potência não confere ganhos adicionais na velocidade de marcha de mulheres pós menopausa - DAMASCENO, Layne Patrícia de Oliveira (2022)
The aging process is associated with declines in the functions of the human body. In women, changes in functional capacities are noticed after menopause. However, the practice of Resistance Training (TR) promotes benefits that mitigate senescent changes. The objective of the study was to evaluate the leg speed from the addition of plyometric power and elastic resistance training to traditional resistance training, within the perspective of minimum dose in post-menopausal women. The sample consisted of 24 women (48-74 years), randomized and divided into three experimental groups: Traditional Minimum Dose (TRDM), consisting of 09 participants; Elastos (ELST), 07 participant; and PLIOMETRY (PLIO), 08 participants.. The gait speed measurements were taken before and after 10 weeks of training, for analysis, the Generalized Estimating Equations (GEE) model with Bonferroni post-hoc was used for analysis, performed in the statistical package SPSS 20.0 with adopted significance of p<0 .05. There was no group*moment interaction, but effects between moments (p<0.00) and groups (p<0.02) were presented. For group effects, only post-hoc significance was shown in the comparison between TRDM and PLIO groups, indicating a greater effect for the Traditional Minimum Dose Group (TRDM) signaling that adding plyometric power exercises does not provide additional gains, at least in the variable measured and in the test used.